The Impact of CEO Successions Involving a Change of Gender on Strategic Change: The Moderating Role of Environmental Factors - Wu, Jie; Richard, Orlando C.; del Carmen Triana, María; Yu, Luman (Journal of Management Studies, 2025)
AbstractPrior research highlights the disruptive and detrimental effects of chief executive officer (CEO) successions that involve a change of gender, i.e., from a male CEO to a female CEO and vice versa. In contrast, we contend that the effects of CEO successions with gender change depend on the context in which they take place. Drawing on expectation states theory, we identify contexts in which each type of CEO succession with gender change can have positive effects on strategic change and subsequent firm performance, depending on whether the degree of gender parity in the context is sufficient for the new CEO to enact strategic changes. Consistent with our arguments, we report findings from Chinese and US samples showing that in the presence of high environmental dynamism female‐to‐male CEO succession yields greater strategic change. Conversely, when environmental dynamism is low, it is male‐to‐female CEO succession that brings about greater strategic change. Furthermore, in the Chinese context, we found that female‐to‐male CEO succession in state‐owned companies results in greater strategic change, whereas male‐to‐female CEO succession has the same effect in privately‐owned settings. Moderated mediation analysis showed that the significant interaction effects on strategic change affect long‐term downstream performance (i.e., Tobin's Q). We discuss implications for theory and practice related to CEO successions.